Effectiveness of a muticomponent workout program integrated in an evidence based multimodal program in hyperfrail elderly patients: POWERAGING randomized clinical trial protocol - González-Sánchez, Manuel; Cuesta-Vargas, Antonio; Rodríguez González, María Del Mar; Díaz Caro, Elvira; Ortega Núñez, Germán; Galán-Mercant, Alejandro; Bedoya Belmonte, Juan José (BMC Geriatr, 2019)
Background: Short-term and mid-term comparison of the efficacy of a multimodal program that incorporates a therapeutic workout program, medication review, diet adjustment and health education, in comparison to the standard medical practice in the improvement of the neuromuscular and physiological condition. Methods: A randomized clinical trial of elderly frail patients drawn from the Clinical Management Unit "Tiro de Pichón", Health District of Malaga, will be included in the study (after meeting the inclusion / exclusion criteria) will be randomized in two groups: a control group that will undergo an intervention consistent of medication review + diet adjustment + health education (regular workout recommendations within a complete advice on healthy lifestyles) and an experimental group whose intervention will consist of a multimodal treatment: therapeutic workout program+ medication review+ diet adjustment + health education. The sociodemographic, clinical and tracing variables will be reflected at the beginning of the study. In addition, the follow-up variables will be gathered at the second and sixth months after the beginning of the treatment and at the third and sixth months after the treatment (follow-up). The follow-up variables that will be measured are: body mass index, general health condition, fatigue, frailty, motor control, attention- concentration- memory, motor memory, spatial orientation, grip strength, balance (static, semi-dynamic), gait speed and metabolomics. A descriptive analysis of the sociodemographic variables of the participants will be conducted. Discussion: A multimodal program that incorporates a therapeutic workout program, medication review, diet adjustment and health education may be effective treatment to reduce the functional decline in elderly.
Keywords: Ejercicio físico; Ancianos - Cuidados; Diet; Elderly; Falls; Frailty; Physical activity; Physical fitness